The productivity limit of manufacturing blood cell therapy in scalable stirred bioreactors. (3rd April 2017) - Bayley, Rachel; Ahmed, Forhad; Glen, Katie; McCall, Mark; Stacey, Adrian; Thomas, Robert
Abstract: Manufacture of red blood cells (RBCs) from progenitors has been proposed as a method to reduce reliance on donors. Such a process would need to be extremely efficient for economic viability given a relatively low value product and high (2 × 10 12 ) cell dose. Therefore, the aim of these studies was to define the productivity of an industry standard stirred‐tank bioreactor and determine engineering limitations of commercial red blood cells production. Cord blood derived CD34+ cells were cultured under erythroid differentiation conditions in a stirred micro‐bioreactor (Ambr™). Enucleated cells of 80% purity could be created under optimal physical conditions: pH 7.5, 50% oxygen, without gas‐sparging (which damaged cells) and with mechanical agitation (which directly increased enucleation). O2 consumption was low (~5 × 10 –8  μg/cell.h) theoretically enabling erythroblast densities in excess of 5 × 10 8 /ml in commercial bioreactors and sub‐10 l/unit production volumes. The bioreactor process achieved a 24% and 42% reduction in media volume and culture time, respectively, relative to unoptimized flask processing. However, media exchange limited productivity to 1 unit of erythroblasts per 500 l of media. Systematic replacement of media constituents, as well as screening for inhibitory levels of ammonia, lactate and key cytokines did not identify a reason for this limitation. We conclude that the properties of erythroblasts are such that the conventional constraints on cell manufacturing efficiency, such as mass transfer and metabolic demand, should not prevent high intensity production; furthermore, this could be achieved in industry standard equipment. However, identification and removal of an inhibitory mediator is required to enable these economies to be realized. Copyright © 2016 The Authors Journal of Tissue Engineering and Regenerative Medicine Published by John Wiley & Sons Ltd.